Environmental characterization in the context of sand extraction in a locality of the municipality of Vila Velha, Espírito Santo, Brazil - Bricalli, Luiza Leonardi (Geografares, 2026)
This article presents an analysis of the environmental conditions and a description of the geological, geomorphological, and pedological aspects of a sand extraction area located in the municipality of Vila Velha, Espírito Santo, Brazil. Its main objective is to evaluate the current environmental conditions associated with sand extraction activities in the area. The methodological approach integrated office-based analyses, including the preparation of thematic maps using a Geographic Information System (GIS) and a review of relevant literature. Field analyses consisted of the identification and macroscopic evaluation of geological, geomorphological, pedological, and environmental characteristics through the description of materials and site features, using geological hammers, hand lenses, and a Brunton compass to assess environmental impacts. A topographic survey was conducted using a total station, and the methodology adopted to calculate the volume of extracted mineral material was based on ABNT Standard NBR 13133/94. The results revealed environmental issues related to sand and clay extraction activities, indicating the need for erosion control measures and containment structures to mitigate the significant environmental impacts associated with clay extraction. Finally, the adoption of vegetative buffer zones and the installation of monitoring wells were recommended to control extraction depth and prevent damage to local soil resources.
Keywords: environmental analysis; sand extraction; environmental monitoring; topography